Level of Service for Pedestrian Movement towards the Performance of Passenger Information in Public Transport Stations in Klang Valley - Ramli, M. Z.; Hanipah, Mohd Hafizal; Lee, L. G.; Loo, K. F.; Wong, J. K.; Zawawi, M. H.; Fuad, N. (AMERICAN INSTITUTE OF PHYSICS INC., 2017)
Rapid growth in car ownership in Malaysia plays a major role to traffic congestion. Hence, public transportation is crucial to cater the residents in high-density area especially in Klang Valley. Signage information in public transport station is one of an important passenger information system. Poor placement of sign information will decrease the efficiency of passenger flow and caused congestion in the station. Passenger information system is very useful for trip planning and decision making. Therefore, it is interesting to study the performance of passenger information system in focusing the movement behavior of pedestrian at non-peak period. Thus, the study on pedestrian movement during non-peak period on weekdays and weekends in mass transit stations and bus transit stations in Klang Valley was carried out by using video observation. The observation of the pedestrian movement was made in Mass Transit Station 1 in the middle of Kuala Lumpur and Mass Transit Station 2 in southern of Kuala Lumpur. The other site was focused at Bus Transit Station 1 in Putrajaya and Bus Transit Station 2 in Kajang. Findings shown that Mass Transit Station 1 having the best facility in terms of passenger information which the level of service obtained is LOS A, while the lowest level of service which is LOS E was obtained in Bus Transit Station 2.